Penguatan Peran dan Fungsi Manajemen Kepala Ruang Melalui Faktor Kepribadian dan Sosial Organisasi - Novita Kurnia Sari; Hanny Handiyani; Rr. Tutik Sri Haryati (Universitas Muhammadiyah Yogyakarta, 2014)
Implementation of leader nurse in roles and functions management to nurses safety was influenced by several factors.The purpose of this study were to investigate the most associating factors that related to implementation of roles and functions management of head nurse in the application of nursing safety. This study used correlative descriptive research method. The research samplewere 40 people and used total sampling techniques. Personality factors and socialorganizations havea signifi cant association with the implementation ofrolesandfunctions management of head nurseto nursing safety application(p= 0,036andp=0,004). Personalityand socialorganizations needed the attention of hospital managementthrough evaluation ofotherfactorsthat could be increasing the implementation of leader nurse roleand function management to application of nurses safety.Key word : Role and functions, management, head nurse, nursing safety